Detection of Di- and Tri-Locus kdr Mutations in Aedes aegypti and Aedes albopictus from Texas, USA, and the Implications for Insecticide Resistance - Bianca M. Wimmer; Cynthia Reinoso Webb; Steven M. Presley (Insects)
During the last 20 years, there has been increasing concern about inefficient vector control efforts due to insecticide resistance. A common mechanism causing insecticide resistance is mutational changes in the voltage-gated sodium channel, deemed knockdown resistance (kdr), resulting from continued pyrethroid application. Although closely related, there have been documented kdr differences and frequencies between Aedes aegypti and Aedes albopictus. Individual Ae. aegypti and Ae. albopictus from five counties in Texas, USA were tested using four single nucleotide polymorphisms genotyping assays to assess the kdr (F1534C, V1016I, V410L, and S989P) differences between the two species. Each mutation was analyzed independently by calculating frequencies and analyzing the difference using a Wilcox Rank Sum test. Significant differences were observed between Ae. aegypti and Ae. albopictus when comparing F1534C and V410L (p-value < 0.0001). Knockdown resistant mutation V1016I was not different between the two species. Individuals from both species had di-locus mutations, and individuals from Ae. aegypti had tri-locus mutations detected in combinations that have been reported to influence insecticide resistance. Given our findings, one can speculate that populations of both species are resistant to pyrethroids, thus likely limiting the success of control methods.